Electronic health records for integrated mental health care: protocol for a scoping review. (2nd January 2021) - Kariotis, Timothy; Prictor, Megan; Gray, Kathleen; Chang, Shanton
ABSTRACT: Objective: Mental health care is known to be poorly integrated into many health systems and could benefit from improved information sharing facilitated by electronic health records (EHRs). Specific issues appear to have limited the application of EHRs in mental health care, including the sensitivity of mental health-related information and issues with data standardisation. This scoping review aims to explore how EHRs have been implemented and adopted in mental health contexts, and their impacts on information sharing. Further, it aims to explore how the unique issues of sensitive information and data standardisation have been addressed in examples of EHRs, if at all. Method: A comprehensive literature search is planned for relevant electronic databases and grey literature sources. Articles from any date that describe the implementation or adoption of an EHR in a mental health context will be included in the review. Articles that describe only the design or development of an EHR in a mental health context will be excluded. Half of the full-text articles will be screened by a second reviewer, with any disagreement mediated by a third reviewer. Results: Abstract screening is currently underway with results being planned for publication in late 2019. The charting of the results will occur in both tabular form and descriptive summaries with results categorised into themes using a deductive content analysis approach. Discussion: The findings from this scoping review have the potential to inform the development of a conceptual framework to guide empirical research on EHRs in mental health contexts.